2023
DOI: 10.1007/s00421-023-05141-3
|View full text |Cite
|
Sign up to set email alerts
|

Mouth rinsing and ingesting salty or bitter solutions does not influence corticomotor excitability or neuromuscular function

Abstract: Purpose To explore the effect of tasting unpleasant salty or bitter solutions on lower limb corticomotor excitability and neuromuscular function. Methods Nine females and eleven males participated (age: 27 ± 7 years, BMI: 25.3 ± 4.0 kg m−2). Unpleasant salty (1 M) and bitter (2 mM quinine) solutions were compared to water, sweetened water, and no solution, which functioned as control conditions. In a non-blinded randomized cross-over order, each solution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
(86 reference statements)
0
0
0
Order By: Relevance
“…Therefore, it is possible that the effect of tasting quinine on corticomotor excitability that was previously observed in the upper limb would be reduced if measured in the lower limb muscles, the latter being more relevant to most exercise contexts. Indeed, we recently found that unpleasant salty or bitter tastes have no influence on knee extensor corticomotor excitability or neuromuscular function in a nonfatigued state (Gray et al, 2023a). Mouth rinsing a salty solution has been shown to ameliorate neuromuscular fatigue (Khong et al, 2020); however, we have found unpleasant salty and bitter tastes to have no influence on knee extensor force characteristics in a fatigued state (Gray et al, 2023b).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Therefore, it is possible that the effect of tasting quinine on corticomotor excitability that was previously observed in the upper limb would be reduced if measured in the lower limb muscles, the latter being more relevant to most exercise contexts. Indeed, we recently found that unpleasant salty or bitter tastes have no influence on knee extensor corticomotor excitability or neuromuscular function in a nonfatigued state (Gray et al, 2023a). Mouth rinsing a salty solution has been shown to ameliorate neuromuscular fatigue (Khong et al, 2020); however, we have found unpleasant salty and bitter tastes to have no influence on knee extensor force characteristics in a fatigued state (Gray et al, 2023b).…”
Section: Discussionmentioning
confidence: 69%
“…However, different from the previous work, we found that the quinine solution had no influence on mean power (Figure 1; −0.1% vs. water and −0.4% vs. control) or peak power (0.4% vs. water and −0.2% vs. control) during the cycling sprint. Furthermore, the salt solution had no effect on mean or peak power, despite a similar unpleasantness and autonomic nervous system response to the bitter condition (Gray et al, 2023a).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations